2019
DOI: 10.1053/j.sult.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI vs PET/CT in Head and Neck Imaging: When, Why, and How?

Abstract: The increasing availability of hybrid PET/MRI systems has led to a breadth of new publications and opportunities for use of PET/MRI. While PET/CT has been a valuable tool for oncologic staging, including head and neck malignancy, there are several theoretical and practical advantages a PET/MRI system would have over PET/CT in head and neck imaging. This review article discusses the established role of PET/CT, early evidence for the role of PET/MRI, and protocol considerations for both PET/CT and PET/MRI as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, it has been suggested that the overlap between the ranges of the ADC measurements can potentially be patched by integrating the DWI along with positron emission tomography/computed tomography (PET/CT) to help in the assessment process. Alternatively, positron emission tomography/magnetic resonance imaging (PET/ MRI) can serve as a replacement to PET/CT in the head and neck region [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that the overlap between the ranges of the ADC measurements can potentially be patched by integrating the DWI along with positron emission tomography/computed tomography (PET/CT) to help in the assessment process. Alternatively, positron emission tomography/magnetic resonance imaging (PET/ MRI) can serve as a replacement to PET/CT in the head and neck region [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous oncology studies have compared the diagnostic performance of PET/MRI with PET/ CT. Consensus among these studies is that despite the differences in attenuation correction methods, statistically significant strong positive correlations between SUV measurements from PET/MR and PET/CT exist (64)(65)(66). It is important to note here that a significant underestimation (67) and overestimation (68) of SUV values on the PET/MRI have been reported.…”
Section: Attenuation Correction For Pet In Pet/mrimentioning
confidence: 74%
“…18 F-FDG is taken up non-specifically by all cells that consume glucose including skeletal muscles, which can cause hinderance in the visualization of tracer uptake in the vessel wall. Other tracers, including 64 Cu-DOTATATE (124), 68 Ga-DOTATOC (125), 18 F-Choline (126) and 68 Ga Pentixafor (127), which are more specific for plaque inflammation, have been explored, but still need to be validated in larger studies. 18-fluorine sodium fluoride ( 18 F-NaF) has been used to identify active calcification showing the potential to visualize microcalcifications which are too small to be seen on MRI or CT (128,129).…”
Section: Petmentioning
confidence: 99%
“…Although PET/CT and MRI are widely used, to our knowledge they are rarely routinely combined for pretherapeutic staging. In addition, hybrid PET/MRI is an emerging diagnostic tool for head and neck cancers 22,23 . In this work, we focus on the role of PET/CT and MRI, whose detection rates of LNMs are approximately 90% 24,25 …”
Section: Discussionmentioning
confidence: 99%